1967
DOI: 10.1002/jez.1401650202
|View full text |Cite
|
Sign up to set email alerts
|

In vitro differentiation of tooth rudiments of embryonic mice. I. Transfilter interaction of embryonic incisor tissues

Abstract: The mandibular incisor rudiment of the 16 day mouse embryo may be separated by enzymatic treatment into an epithelial covering and an inner mesenchyma1 papilla. Each separated tissue fails to differentiate when grown singly in vitro, but odontocytes, amelocytes, and their extracellular matrices are noted in cultures of recombined tissues. Separated tissues also fail to differentiate on collagen gels. Both the mesenchymal papilla and the internal dental epithelium differentiate when placed on opposite sides of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The isolated component of embryonic mouse tooth germs, either epithelium or mesenchyme fails to undergo cytodifferentiation, and the epithelium dies when grown in isolation [21]. However, physical separation by Millipore filter between epithelium and mesenchyme allows enamel organ and papilla differentiation with the deposition of matrix.…”
Section: Growth Factors Mediate Inductive Interactions During Odontogmentioning
confidence: 99%
“…The isolated component of embryonic mouse tooth germs, either epithelium or mesenchyme fails to undergo cytodifferentiation, and the epithelium dies when grown in isolation [21]. However, physical separation by Millipore filter between epithelium and mesenchyme allows enamel organ and papilla differentiation with the deposition of matrix.…”
Section: Growth Factors Mediate Inductive Interactions During Odontogmentioning
confidence: 99%
“…To investigate interactions underlying the development of skeletal assemblies unique to Okada, 1955;Holtfreter, 1968;Drews et al, 1972;Corsin, 1975Tyler, 1978Bee and Thorogood, 1980;Hall, 1978, 1981aHall, 1981bKoch, 1967Thesleff and Hurmerinta, 1981 'Probable interactions based on tissue relations.…”
Section: Patterning Of Neural Crest Populationsmentioning
confidence: 99%
“…These processes involve a series of inductive and permissive interactions that lead to determination, differentiation, growth, and organization of odontogenic tissues. Both dental epithelium and mesenchyme are essential for tooth formation (McCarrol and Dahlberg, 1934;Koch, 1967). Classical tissue recombination experiments have demonstrated that the odontogenic potential, the capability of a tissue to instruct an adjacent tissue to form a tooth, arises in dental epithelium initially, and then at E12.5 shifts to dental mesenchyme where it remains in the dental papilla till birth (Yoshikava and Kollar, 1981;Mina and Kollar, 1987;Lumsden, 1988).…”
Section: Introductionmentioning
confidence: 99%